Abnormal Regional Homogeneity and Functional Connectivity of Baseline Brain Activity in Hepatitis B Virus-Related Cirrhosis With and Without Minimal Hepatic Encephalopathy - Sun, Qing; Fan, Wenliang; Ye, Jin; Han, Ping (Frontiers in Human Neuroscience, 2018)
Background and Aims: Abnormalities in neural activity have been reported in cirrhosis with minimal hepatic encephalopathy (MHE). However, little is known about the neurophysiological mechanisms in this disorder. We aimed to investigate the altered patterns of regional synchronization and functional connections in hepatitis B virus-related cirrhosis (HBV-RC) patients with and without MHE using both regional homogeneity (ReHo) and region of interest (ROI)-based functional connectivity (FC) computational methods. Methods: Data of magnetic resonance imaging scans were collected from 30 HBV-RC patients with MHE, 32 HBV-RC patients without MHE (NMHE) and 64 well-matched controls. Several regions showing differences in ReHo after one-way analysis of variance were defined as ROIs for FC analysis. Next, post-hoc t-tests were applied to calculate the group differences in ReHo and FC (false discovery rate correction, p < 0.05). Correlations between clinical variables and the altered ReHo and FC were then assessed in patient groups. Results: Across three groups, significant ReHo differences were found in 9 ROI regions mainly within the visual network (VN), dorsal attention network (DAN), somatomotor network (SMN), frontoparietal control (FPC) network and thalamus. Compared with HC, the MHE group exhibited abnormal FC mainly between the right calcarine (CAL.R) and MFG.L/right thalamus. The MHE patients showed increased FC between the MFG.L and CAL.R compared to NMHE patients. Disease duration of MHE patients was positively correlated with increased mean ReHo values in the right fusiform gyrus; PHES test scores were negatively correlated with increased FC between MFG.L and CAL.R and positively correlated with reduced FC between the CAL.R and THA.R. For NMHE patients, the mean ReHo values in the right frontal pole were positively correlated with disease duration and positively correlated with the PHES scores. Conclusion: Our results exhibited that the functional brain modifications in patients with and without MHE are characterized by compound alterations in local coherence and functional connections in the VN, SMN, DAN, FPC networks and thalamus by using a combination of ReHo and ROI-based FC analysis. These functional imaging changes are correlated with disease duration/PHES. This study helped us gain a better understanding of the features of brain network modifications in cirrhosis.